Islamic hospital tourism in Indonesia: A literature review - Putranto, Ega Dwi; Aini, Qurratul (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Islamic hospital tourism refers to the practice of seeking medical treatment in healthcare facilities that adhere to Islamic principles, offering services that align with the cultural and religious values of Muslim patients. The Islamic hospitals provide worship facilities and guidance for patients, visitors, and employees, ensure halal and safe nutrition for patients, and offer medical treatment services that respect gender-specific needs. Purpose: To provide an in-depth analysis of the current state of Islamic hospital tourism in Indonesia, highlighting its benefits and challenges. Method: The type of research used is library research. Secondary data from earlier research investigations was used in this investigation. The selected journals are journals related to Islamic hospital tourism in Indonesia. Results: Based on the results of the article analysis, ten articles were found to be appropriate. Four articles were about public preferences for Islamic sharia hospitals, three articles were about halal medical tourism, two articles were about international Islamic standards for medical tourism providers and one article was waqf in the health sector. Conclusion: The benefits of Islamic hospital tourism in Indonesia are halal healthcare services, sharia-based facilities, patient satisfaction and loyalty, competitive advantage, and positive sentiment and business potential. Challenges of Islamic hospital tourism in Indonesia are lack of standardization, infrastructure and capacity, regulatory framework, and integration with tourism industry.